Nilai-Nilai Moderasi Beragama Dalam Perspektif Filsafat Manusia Ali Syariati - Zulkarnain, Ahmad (Indonesia, 2023)
This article departs from the phenomenon of religious intolerance in Indonesia which is increasingly alarming. In Indonesia alone, it was recorded that since 2022 there have been 175 violations of religious freedom with 333 actions. this data tends to increase from the previous year's figures, which were 171 events with 218 actions. The purpose of this research is to provide a new perspective on religious moderation through Ali Syariati's human philosophy, and to provide an understanding of how to understand religion and the values of tolerance contained therein. The approach in this research is descriptive qualitative with literature review method or literature study. The data collection method used in this research is through a review of relevant literature from various sources that are in accordance with the research topic. The results of this study are first, humans were created on this earth as a caliph or leader in which a leader must have an attitude of tolerance and willingness to accept differences. From the attitude of a tolerant leader, it can then be categorized as values in religious moderation. Second, insan as a moderate human characteristic because it always proceeds towards perfection or goodness. Meanwhile, basyar is categorized as an intolerant human being because it always leads to ugliness and disgrace